Adoption of Sharing and Reuse of Open Resources by Educators in Higher Education Institutions in the Netherlands: A Qualitative Research of Practices, Motives, and Conditions - Schuwer, Robert; Janssen, Ben (International Review of Research in Open and Distributed Learning, 2018)
To find out what is needed to speed up the adoption of open sharing and reuse of learning materials and open online courses in publicly funded Dutch institutions of Higher Education, a qualitative research study was conducted in fall 2016. This study examined issues of willingness of educators and management, barriers and enablers of adoption, and the role of institutional and national policy in the adoption of open sharing and reuse of learning materials and online courses. Fifty-five stakeholders (educators, board members, and support staff) in 10 Dutch Higher Education Institutions were interviewed. The main findings of this study are: motivation for sharing and reuse of learning materials for educators and managers is directly related to the ambition to achieve better education for students; sharing and reuse of learning materials is common practice, very diverse and not open accessible for the whole world, and important barriers include lack of awareness of opportunities for open sharing and reuse and lack of time. Based on the findings from the interviews, the last section of this paper presents conclusions and recommendations regarding how Dutch institutions for Higher Education can formulate effective policies to raise awareness, organize adequate support and provide time to experiment.